1998
DOI: 10.1037/0278-6133.17.5.445
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for stages of health behavior change: The precaution adoption process model applied to home radon testing.

Abstract: Hypotheses generated by the precaution adoption process model, a stage model of health behavior, were tested in the context of home radon testing. The specific idea tested was that the barriers impeding progress toward protective action change from stage to stage. An intervention describing a high risk of radon problems in study area homes was designed to encourage homeowners in the model's undecided stage to decide to test, and a low-effort, how-to-test intervention was designed to encourage homeowners in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(179 citation statements)
references
References 21 publications
(33 reference statements)
2
160
1
8
Order By: Relevance
“…Although test orders were found to be unrelated to the degree of threat presented in the brochures, self-reported risk likelihood, risk seriousness, and concern were strongly correlated with intentions to test as well as test orders. Two further studies support the idea that perception of radon as a health risk is related to intentions to conduct radon testing or mitigation (Duckworth et al, 2002;Weinstein et al, 1998), but no studies reviewed examined radon risk perception and testing specifically among vulnerable rural populations receiving public health nursing services. Specific focus on rural populations is warranted because knowledge gained will inform health policy and clinical practice interventions to address disparate health outcomes.…”
Section: Correlates Of Radon Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although test orders were found to be unrelated to the degree of threat presented in the brochures, self-reported risk likelihood, risk seriousness, and concern were strongly correlated with intentions to test as well as test orders. Two further studies support the idea that perception of radon as a health risk is related to intentions to conduct radon testing or mitigation (Duckworth et al, 2002;Weinstein et al, 1998), but no studies reviewed examined radon risk perception and testing specifically among vulnerable rural populations receiving public health nursing services. Specific focus on rural populations is warranted because knowledge gained will inform health policy and clinical practice interventions to address disparate health outcomes.…”
Section: Correlates Of Radon Testingmentioning
confidence: 99%
“…Because radon testing behaviors have been positively associated with risk perception of exposure (Weinstein, Lyon, Sandman, & Cuite, 1998), an understanding of the accuracy of community dwellers' risk perceptions and the variables associated with elective testing for radon would enable nurses to appropriately target at-risk populations for education. Studies have examined selected sociodemographic predictors of radon testing behavior and have found that community dwellers generally have superficial knowledge about radon and that testing behavior is negatively associated with being female, belonging to a minority group, having a lower education and family income, and increasing age (Ferng & Lawson, 1996;Halpern & Warner, 1994).…”
Section: Correlates Of Radon Testingmentioning
confidence: 99%
“…Although guidelines suggest immediate interven-tion for behaviors to facilitate weight loss, behavioral change may be difficult unless patients are primed or ready for change. Patient movement along behavioral stages such as those described in the Transtheoretical Model 17,18 or the Precaution Adoption Process Model (PAPM) 19,20 may be a necessity. For stage progression to occur, especially in a model such as the PAPM where "unaware" and "unengaged" stages exist, patients may first need to "perceive" that weight is a relevant medical issue.…”
Section: Introductionmentioning
confidence: 99%
“…How many people are aware that the threats are severe? According to Weinstein, Lyon, Sandman, & Cuite (1998), the most crucial stage in prevention strategy is to make people pay attention, become aware and take serious steps towards a risk. PMT consists of five important stages.…”
Section: Literature Reviewmentioning
confidence: 99%